2017
DOI: 10.3349/ymj.2017.58.1.248
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of Right Ventricular Free Wall Following Ventricular Septal Rupture in Takotsubo Cardiomyopathy with Right Ventricular Involvement

Abstract: Most patients diagnosed with takotsubo cardiomyopathies are expected to almost completely recover, and their prognosis is excellent. However, complications can occur in the acute phase. We present a case of a woman with takotsubo cardiomyopathy with right ventricular involvement who developed a rupture of the right ventricular free wall following ventricular septal rupture, as a consequence of an acute increase in right ventricular afterload by left-to-right shunt. Our case report illustrates that takotsubo ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Mitral regurgitation can be caused by leaflet tethering due to geometrical changes in the LV (according to TS pattern) and the displacement of the papillary muscles or by SAM [ 53 , 54 ]. Although a rare instance, LV free wall or interventricular septal rupture may occur [ 55 , 56 , 57 , 58 , 59 ]. Apical akinesia may promote intraventricular thrombosis and furthermore thromboembolic events may occur [ 56 , 60 ].…”
Section: Standard Echocardiographymentioning
confidence: 99%
“…Mitral regurgitation can be caused by leaflet tethering due to geometrical changes in the LV (according to TS pattern) and the displacement of the papillary muscles or by SAM [ 53 , 54 ]. Although a rare instance, LV free wall or interventricular septal rupture may occur [ 55 , 56 , 57 , 58 , 59 ]. Apical akinesia may promote intraventricular thrombosis and furthermore thromboembolic events may occur [ 56 , 60 ].…”
Section: Standard Echocardiographymentioning
confidence: 99%
“…Although a few papers reported that the earliest time of recurrence was 8 days [4,6], in most cases, a relapse occurs within a few months or years [1,4,6,[9][10][11][12][13]. Severe complications, including arrythmia, acute cardiac shock and cardiac rupture may arise [1,4,[14][15][16][17][18]; however, takotsubo cardiomyopathy is typically a reversible functional disorder and autopsy cases are rare [19]. In most cases, macroscopic study of the heart shows focal damage, such as rupture, or the absence of structural change [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…This can lead to left ventricular rupture and recent studies reported right ventricular involvement in 28% -50% [9] [10], the friable right ventricle susceptible to rupture due to mechanical wall stress in biventricular Takotsubo cardiomyopathy [11]. Isolated RV free wall rupture as a complication of inferior wall and right ventricular myocardial infarction is an uncommon finding in transthoracic echocardiographic examination [12] and it was reported in Figure 1 to Figure 6.…”
Section: Introductionmentioning
confidence: 99%